REDUKSI BIJIH MANGAN - Agus, Jasdar; Edysul Isdar,; Aruyo Suharyanto, (SAINFIS: Jurnal Sains Fisika, 2022)
Manganese ore extraction has been carried out using the reduction method. The purpose of this study was to determine the content of manganese ore before and after the roasting process. Prior to manganese ore reduction, manganese ore samples were characterized by XRF and XRD. Characterization was carried out to determine the chemical composition of the manganese ore. The roasting process is carried out by mixing 1500 grams of manganese ore with 300 grams of wood charcoal at a temperature of 700˚C for 2 hours. The roasting process is carried out to change the manganese ore phase from MnO2 to MnO. Changing the phase to MnO is very important because Mn4+ is relatively stable in acidic solutions so as to facilitate the manganese dissolution process. There are differences in the chemical composition of manganese ore before the roasting process and after the roasting process. The roasting process was carried out at a temperature of 700 C for 2 hours. To determine the chemical composition of manganese ore, characterization was carried out using XRD. Where manganese ore that has not gone through the roasting process has a chemical composition of 29.14% MnO2. Meanwhile, manganese ore that has been roasted has a chemical composition of 40.09% MnO2.